2021
DOI: 10.1021/acs.cgd.1c00647
|View full text |Cite
|
Sign up to set email alerts
|

A Photochromic Zinc–Viologen Framework with a High-Contrast Nonlinear Optical Switchable Behavior

Abstract: As an important branch of nonlinear optical (NLO) switches, second-harmonic-generation (SHG) switches undergoing reversible SHG-on and SHG-off states upon external stimuli exposure have been the focus of intense scientific research due to their potential applications in photoelectric technologies. The high-contrast switching of SHG, a key issue for the potential applications of SHG optical switches, has been a challenge but is undoubtedly very interesting. Incorporating stimuli-responsive molecules into the SH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Organic–inorganic hybrid materials have attracted considerable attention because of their flexible structure and remarkable properties, such as photovoltaic, ferroelectric and. piezoelectric, and nonlinear optical (NLO) properties. Among them, layered two-dimensional (2D) organic–inorganic halide perovskites (as an emerging semiconducting materials, they possess a strong quantum confinement effect to achieve high PLQYs and, moreover, photochromism can also be adjusted by halogen) have widespread applications in solar cells, , light emitting diodes (LEDs), and photodetectors. …”
Section: Introductionmentioning
confidence: 99%
“…Organic–inorganic hybrid materials have attracted considerable attention because of their flexible structure and remarkable properties, such as photovoltaic, ferroelectric and. piezoelectric, and nonlinear optical (NLO) properties. Among them, layered two-dimensional (2D) organic–inorganic halide perovskites (as an emerging semiconducting materials, they possess a strong quantum confinement effect to achieve high PLQYs and, moreover, photochromism can also be adjusted by halogen) have widespread applications in solar cells, , light emitting diodes (LEDs), and photodetectors. …”
Section: Introductionmentioning
confidence: 99%
“…Photochromic materials, a crucial subclass of intelligent species, have two switchable stable or metastable states with contrasting colors and physical properties. [1][2][3][4][5] Including photochromic functional motifs [6,7] into semiconductors confers intelligent behavior and color-related applications on semiconductors. For instance, Hecht, Samorì, and colleagues created optically switchable transistors by incorporating photochromic molecules into semiconducting polymer matrices; [8,9] we developed and implemented the ideas of color-indicating smart circuit protection [10,11] and color-and-electricity-indicating dualmode radiation detection and imaging [12] based on singlecomponent viologen-based photochromic semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Past studies have shown that the majority of switching SHG compounds exhibit single-step transformation between NCS (SHG-on) and CS structure (SHG-off ) by an external stimulus. [12][13][14][15][16][17] For example, single-component molecular crystal 2-(hydroxymethyl)-2-nitro-1,3-propanediol exhibits a high contrast SHG-on/off ratio at around the phase transition temperature of 340 K, 18 the pressure-controlled SHG-on/off of CdTeMoO 6 , 19 thermally-induced inverse SHG off/on of K x (NH 4 ) 2−x PO 3 F (x = 0-0.3), 20 and both photo-and heatinduced SHG-switching behaviors of β-[(MQ)ZnCl 3 ] (MQ + = N-methyl-4,4′-bipyridinium). 21 Other examples are representative NCS (SHG-high) to NCS (SHG-low) materials, such as (R/S)-3-quinuclidinol 22 and (BA) 2 (EA) 2 Pb 3 I 10 .…”
Section: Introductionmentioning
confidence: 99%